2018
DOI: 10.1037/ccp0000264
|View full text |Cite
|
Sign up to set email alerts
|

Mental health care consumers’ relative valuing of clinician performance information.

Abstract: Harnessing clinician information to make more personalized and informed treatment decisions could potentially promote better treatment engagement, retention, and outcomes. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…The same method with racial–ethnic participants found that they had much stronger preferences for therapist multicultural training and use of culturally adapted treatments than they did for simple racial–ethnic matching with their therapists (Swift, Callahan, Tompkins, Connor, & Dunn, ). More recently, Boswell and colleagues () used this method to examine preferences for clinician performance information.…”
Section: Definitions and Measuresmentioning
confidence: 99%
“…The same method with racial–ethnic participants found that they had much stronger preferences for therapist multicultural training and use of culturally adapted treatments than they did for simple racial–ethnic matching with their therapists (Swift, Callahan, Tompkins, Connor, & Dunn, ). More recently, Boswell and colleagues () used this method to examine preferences for clinician performance information.…”
Section: Definitions and Measuresmentioning
confidence: 99%
“…Finally, there is reason to believe that clinicians might be open to such a case assignment system. In several studies, clinicians reported positive attitudes toward ROM generally and toward a system that would aid in identifying specific patients with whom they have a high likelihood of treating successfully (Boswell et al, 2016(Boswell et al, , 2018. Thus, it is plausible that this type of case assignment system could be a practical method for maximizing improvement and minimizing harm or no-change rates for a given MHC system.…”
Section: Using Rom To Improve Mhc Systems: Empirical Supportmentioning
confidence: 99%
“…improve patient-level outcomes, the empirical evidence is fairly clear: ROM reduces instances of harm or deterioration and increases improvement rates (Lambert et al, 2018), which can benefit all stakeholders (and help to decrease any maleficence). Moreover, there are no empirical data to suggest that the use of such systems unduly burdens patients or providers; in fact, both stakeholder groups tend to value ROM (Boswell et al, 2018;Moltu et al, 2018). In contrast, the various possible uses of psychotherapist-level ROM data by administrators (e.g., for case-assignment or clinician training efforts) are associated with more complex and nuanced ethical considerations.…”
Section: Ethical Implications Of Rom At the Systems Levelmentioning
confidence: 99%
“…Research has shown that not all therapists are similarly effective (61)(62)(63). Yet, patients wish to obtain information on their therapist's performance level (64). Therefore, it is very important to discuss with a patient the possibility that a mismatch between the patient and the therapist may limit potentially beneficial treatment effects, in order to avoid the patient to conclude that an unsuccessful course of treatment was his or her own fault.…”
Section: Discussing the Evidence Openly With The Patientmentioning
confidence: 99%